Fumonisins B1 + B2 change the expression of genes in apoptosis balance in Nile tilapia fingerlings - Claudino-Silva, Stefânia C.; Lala, Bruno [UNESP]; Mora, Natália H.A.P.; Schamber, Christiano R.; Nascimento, Carlos S.; Pereira, Vinícius V.; Hedler, Dayne L.; Gasparino, Eliane (Elsevier, 2018)
In this study, we tested the hypothesis that the ingestion of feed containing fumonisin affects the apoptosis balance in liver cells. Thus, a trial was conducted with Nile tilapia fingerlings (2.64 ± 0.06 g) fed diets containing increasing levels of fumonisin (FB) (0-control diet, 20, 40, and 60 mg/kg), and expression of caspase7 (CASP7) and sphingosine phosphate lyase (SPL) genes in liver tissue was evaluated at 15 and 30 days of treatment. SPL:CASP7 mRNA ratio was also evaluated. Relative mRNA levels of SPL decreased in tilapia treated with 60 mg FB/kg of diet at 15 days (P <.0001), while a significant increase in SPL was detected at the two highest levels of inclusion at 30 days (P <.0001). CASP7 gene expression decreased linearly as fumonisin was added, at 15 days (P <.0001). At 30 days, however, the relative CASP7 mRNA levels were only reduced in the tilapia treated with 60 mg FB/kg of diet (P =.0011). The results obtained in this study suggest a direct relationship between SPL and CASP7 expressions, so it can be inferred that as the period of consumption and level of fumonisin are increased, the numerical relationship between SPL:CASP7 mRNA is also increased.
Keywords: Fumonisin; Gene expression; Mycotoxin; Oreochromis niloticus